(untitled) (Journal of the College of Education for Women, 2019)
China is the first Asian country in the Far East that has been invaded by a foreign power, after following a policy of isolation against the outside world. Although Britain was the first foreign power that penetrated China and had many concessions within its lands, it was not the only one that directed its interests toward china. Russia was one of the powers which were interested in China, considering the special relationships that related together the neighboring countries, like the problematic boundaries. However, after World War II, the Soviet Union tries to extend its influence and power over Asia, and China was the first country that fell under the campaign on the Soviet Union. In spite of the fact that the political role of the United States didn’t become clear till the World War II, her role was still clear in china since launching the open door policy in 1899, and managed to have the china to its side in the world war I, and the American support to the national Chinese government during 1920s against the communist invasion. The importance of studying "The Russian and American Ambitions in China 1842-1945" comes from the fact that this period under discussion is the time when the roots for the cold war started to grow, the war that started since the end of the World War II till the collapse of the Soviet Union in 1989.